An introduction to community dance practice - Amans,Diane (Palgrave, 2017)
This updated second edition of an essential introduction to community dance practice offers a far-reaching and accessible overview of the industry from eminent practitioners. Packed with case studies, interviews and resources, the text addresses the latest developments and prepares students and practitioners for the realities of employment.